2007
DOI: 10.1002/ajmg.a.31809
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel mutations in WFS1 and genotype–phenotype correlation in Wolfram syndrome

Abstract: Mutations in the WFS1 gene have been reported in Wolfram syndrome (WS), an autosomal recessive disorder defined by early onset of diabetes mellitus (DM) and progressive optic atrophy. Because of the low prevalence of this syndrome and the recent identification of the WFS1 gene, few data are available concerning the relationships between clinical and molecular aspects of the disease. Here, we describe 12 patients from 11 families with WS. We report on eight novel (A214fsX285, L293fsX303, P346L, I427S, V503fsX51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
59
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 32 publications
(38 reference statements)
10
59
1
Order By: Relevance
“…Similarly, Hardy et al in a national UK cohort, found no clear correlation between any of the observed mutations and disease severity (15). However, Cano et al studying French patients and combining his results with those of five published studies, including the data of Hardy et al found that the presence of two inactivating mutations predisposed patients to an earlier age of onset of both diabetes mellitus and optic atrophy (24). On the other hand, we observed a milder phenotype in a patient carrying a homozygous missense mutation in exon 5.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, Hardy et al in a national UK cohort, found no clear correlation between any of the observed mutations and disease severity (15). However, Cano et al studying French patients and combining his results with those of five published studies, including the data of Hardy et al found that the presence of two inactivating mutations predisposed patients to an earlier age of onset of both diabetes mellitus and optic atrophy (24). On the other hand, we observed a milder phenotype in a patient carrying a homozygous missense mutation in exon 5.…”
Section: Discussionmentioning
confidence: 90%
“…36 We analyzed as mutations (i) c.2020G→A (p.Gly674Arg), considered either a mutation 37 or a polymorphism, 38 and (ii) c.1367G→A (p.Arg456His), considered either a mutation 34 or a polymorphism, [31][32][33]39,40 because both are predicted to produce deleterious proteins by Condel 41 and PolyPhen-2. 42 c.2020G→A is also considered a mutation in the LOVD-WFS1 database.…”
Section: Patientsmentioning
confidence: 99%
“…We considered as polymorphisms c.*47C→T 33,43,44 and c.*253G→A 37 because they locate to the 3′-untranslated region of WFS1 mRNA, and c.316-37C→T because its effects on splicing have not been indicated. 34 Supplementary Table S2 online lists all the mutations described in the patients.…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations